Hairpin Windings: An Opportunity for Next-Generation E-Motors in Transportation - Nuzzo, Stefano; Barater, Davide; Gerada, Chris; Vai, Piermaria (IEEE Industrial Electronics Magazine, 2022)
Advances in electrical machines and power electronics (PEs) are helping to achieve the power density and efficiency required by the transportation sector. However, the reliability of components and production processes is a challenge. This is especially true for electrical machines, whose winding processes are far from the high levels of automation, programmability, and repeatability that are required. This article looks into hairpin windings and outlines a number of future actions to address challenges and eventually enable the complete penetration of hairpin windings in transportation.
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering